Homogeneous and Stratified Liquid-Liquid Flow Effect of a Viscosity Reducer: I. Comparison in parallel plates for heavy crude - Suarez-Dominguez, E. J.; Izquierdo-Kulich, E. F.; Rodríguez-Valdez, A.; Solorio-Ordaz, F.; Chavez-Castellanos, A. E.; Palacio-Perez, A. (Engineering, Technology & Applied Science Research, 2016)
Production of heavy crude oil in Mexico, and worldwide, is increasing which has led to the application of different methods to reduce viscosity or to enhance transport through stratified flow to continue using the existing infrastructures. In this context, injecting a viscosity improver that does not mix completely with the crude, establishes a liquid-liquid stratified flow. On the basis of a parallel plates model, comparing the increase of flow that occurs in the one-phase case which assumes a complete mixture between the crude and the viscosity improver against another stratified liquid-liquid (no mixing between the oil and compared improver); it was found that in both cases there is a flow increase for the same pressure drop with a maximum for the case in which the flow improver is between the plates and the crude.